Corporate Social Responsibility Disclosure During Pandemic: What Does the Female Supervisory Board Do? - Satrio, Arif Budi (Universitas Bangka Belitung, 2024)
There have been many investigations regarding the role of women's boards in firms, especially from an economic point of view, but very rarely from a social perspective. This study provides novelty by raising the topic of the female supervisory board on the disclosure of corporate social responsibility information at the beginning of the recent health crisis period, namely the COVID-19 pandemic. Investigations conducted on 465 non-financial firms in Indonesia show new evidence that female supervisory boards did not focus on corporate social responsibility issues during the pandemic. The results of this robust investigation can be useful for regulators and academics in developing countries at a time of high business uncertainty.